Ser ou não ser bilíngue: os posicionamentos subjetivos de uma professora de inglês diante do outro - Arabela Vieira dos Santos Silva e Franco (2016)
The notion of bilingual individual dates back to ancient times; however, until nowadays science has not yet reached an agreement on the parameters that circumscribe the specificities of bilingualism. There are many proposals ranging from a minimum of knowledge in at least two languages to the extreme degree of proficiency in all languageskills. To make this spectrum even wider, a psychoanalytic approach would offer us the possibility to treat bilingualism as an individual phenomenon, by analyzing how each human subject is discursively inscribed as a bilingual subject. This approach assumes thepresupposition that it is within the discourses, in the relation between the subject and the Other, which is the symbolic place that can be occupied by several elements such as a certificate, a native, a teacher, a co-worker, etc., that the subject will emerge. Therefore, there will not be enough signifiers to define a subject as bilingual. Due to the specificitiesof ConCol, a continuing education program for English language teachers, the corpus was collected by using an adaptation of the Conversational methodology, which we called Conversational Round. The analysis of the utterances were made according to Lacan'ssignifier theory and his theory of the four discourses. The signifying chains produced by a teacher concerning the issue of bilingualism were analyzed highlighting the relationship between the signifiers produced and her utterances concerning her speaking and writing skills in English and in Portuguese. I could notice some turns in her discursive positions,but I have not noticed any considerable subjective changes considering her position as a bilingual subject, or in relation to her speaking and writing skills. The main result of this research was to realize that the definition of a bilingual subject goes beyond the uniqueness of each subject, since in every discursive turn the subject takes mightdetermine whether they consider themselves bilingual or not. Therefore, any attempt to signify the subject will be as evanescent as their positions within the discourses. Thus, this research might contribute to studies that take into consideration the impossible when dealing with languages, the impossible that goes beyond the prescriptive grammatical and linguistic categories, being the subject division itself the singular way of each individual to deal with their division.